ON CHARACTERIZATIONS ON THE SURFACES OF ROTATION FORMED BY MAGNETIC CURVES IN Q2 ? E13 - Almaz, Fatma; Kulahci, Mihriban Alyamac (Taru Publications, 2023)
In this paper, the different magnetic fields on the setting out particle trajectories according to the magnetic flow attached by the Killing magnetic field are given in Q(2) subset of E-1(3). The surfaces generated by the Killing magnetic field of the y-magnetic curve are expressed according to asymptotic orthonormal frame field {eta, beta, y} in Q(2) subset of E-1(3) and, using Clairaut's theorem the conditions being geodesic on these surfaces of rotation are given. Also, the curvatures and the kinetic energy and angular momentum of the surfaces of rotation formed by y-magnetic curve are examined.
Keywords: Clairaut's theorem; Lightlike cone; Magnetic curves; Specific kinetic energy; Specific angular momentum